Інформаційна система “карта ХНУРЕ” - Світенко, Г. М. (ХНУРЕ, 2020)
Digital map of NURE, in the form of web application, which is designed to help first year students to find the fastest path to required place in all campuses of NURE. All campuses of NURE are digitalized and stored in two data formats: vector images for plans and a graph with information about places in campuses, which is stored in .json file. For finding the best way, application uses Dijkstra's algorithm.